BEHAVIORAL BIASES AND THEIR IMPACT ON FINANCIAL PERFORMANCE IN THE CONTEXT OF FINANCIAL LITERACY: A LITERATURE REVIEW - Hussein Jawad Kadhum; Hussein Kareem Saidi (Scholar Express Journals, 2022)
The main objective of the study is to systematically review literature that addressed behavioral biases and their relationship to financial performance in the presence of financial Literacy or not, focusing on the main gap in current studies, and then looking for Findings that achieve the best level for selected study. We used the inductive approach by conducting a comprehensive survey on published articles for the period (2009-2021), which requires determining the goals and findings. After identifying the literature that reviewed the variables of the study, it was concluded that most of the findings indicate that behavioral biases affect financial performance, while financial literacy improves the level of performance. The researchers found that none of the previous studies focused on the above-mentioned variables in the Iraqi banking sector
Keywords: Behavioral Finance; Emotional Biases; Cognitive Biases; Investment Decisions